KENYAMANAN RUANG PERPUSTAKAAN DENGAN PRINSIP GREEN OFFICE - Endang Fatmawati (Perpustakaan IPB, 2019)
The concept of an environmentally friendly library office can cut operating costs. The impact of excessive energy consumption is one of the factors behind the need to conceptualize library space with the green office principle. Librarians as the main actors who manage the library, must be trained and have the competence to realize the green office. In the context of college library space, the green office can be explained as a concept for managing an environmentally friendly work environment and reducing the adverse effects of space building on the campus environment. The management in question includes: designing, building, and maintaining rooms to increase productivity for the inhabitants of the library. The library office is designed to collaborate with the surrounding environment whose activities are carried out with environmentally friendly principles. The goal is that the work environment in the library will be a comfortable, conducive, clean, shady, beautiful and healthy place for the knowledge-takers who are in it. Some programs that can be done include representative buildings, flexible space design, energy efficiency, power management features; saving water; resources efficiency; green information technology; physical design; waste management; air quality; minimize noise; space design; air freshener; or utilizing scrap paper. Keywords: environmentally friendly, green office, energy saving, library, convenience